Phage Predation Shapes the Population Structure of Shiga-Toxigenic Escherichia coli O157:H7 in the UK: An Evolutionary Perspective - Cowley, Lauren A.; Dallman, Timothy J.; Jenkins, Claire; Sheppard, Samuel K. (Frontiers in Genetics, 2019)
Bacterial–host interactions are non-linear and actually threefold, involving significant selection through predatory lytic bacteriophages in the host environment. In studies of human and animal gut microbiome bacteria, it is important to consider phage in all host–pathogen interactions. We use an important zoonotic pathogen, Shiga toxigenic Escherichia coli (STEC) O157:H7, to investigate this. Our study provides evidence that phage resistance profiles are well maintained at the sub-lineage level with variation in profiles within sub-lineages uncommon. This indicates that phage resistance heterogeneity happened early on in the STEC O157:H7 natural history and that occasional “wobbles” do not often outcompete the stable lineage unless combined with a competitive advantage. We discuss an example of this in the acquisition of stx2a that, while an important virulence factor, also conveys increased phage cross-resistance. We also discuss the role of phage resistance in co-occurrence of the three stable lineages worldwide and whether differing phage resistance is maintaining diversity.